Viabilidade ambiental da suinocultura na microbacia do Rio Mandurim Município de Marmeleiro - PR - Rech, Clóvis (2006)
This work had as objective to study the environmental viability of the swine breeding activity in the basin of the river Mandurim, which is located in the Southwest area of the of Paraná state. It was appraised the physiographic characteristics of the basin, with the determination of the principal uses and occupations of the soil related with the strips of steepness, characterization of the properties with relationship to the number of swine, storage structures and capable areas for application of the dejections. I, it was evaluated quality of the water river Mandurim in the space where the swine breeding activity is developed. The main results indicate that the micro basin presents enough capable areas to receive all the swine s dejections, however, in all the properties, the dung hills present insufficient storage capacity, with deficit varies from strip of 8 m3 to 276 m3, besides 12 units (63%) that are located in a permanent preservation area . The analyses of the water revealed increment of organic matter, measure like DQO and DBO, among the amount points of the swine breeding are of swine breeding, although none cannot affirm that the area swine activity is the only responsible for that increase. The other parameters, such as nitrogen, match and dissolved oxygen, in general, assisted to the quality pattern for rivers class two.